Optimization of TiO2-based UV-LED Photocatalytic System for Mixed Dyes and Pharmaceutical Contaminants - Chen, Zexiang; Kang, Xue; Wang, Chen; Li, Yongguo (Bulletin of Chemical Reaction Engineering & Catalysis, 2024)
To optimize the working efficiency of the novel UV-LED system based on TiO2 photocatalyst, the influence mechanism of LED lamp arrangement, light source wavelength and working voltage on photocatalytic efficiency was investigated. Acid red 26 (AR 26), acetaminophen (ACT) and diclofenac (DCF) were used as contaminant targets of the photocatalytic system. LED lamp arrangement had almost no effect on the degradation of AR26. However, the degradation efficiency of ACT and DCF was improved under a higher light uniformity. The ACT concentration and DCF concentration at 360 min decreased by 14% and 15%, respectively, with increasing light distribution from 45% to 66.5%. The main reason for this discrepancy in effect was whether the rate-determining step of the degradation mechanism was affected by the light uniformity. The short wavelength and high working voltage of LEDs were conducive to the photocatalytic degradation of contaminants to a different degree. When the wavelength was reduced from 405nm to 365nm, the conversion of AR26, ACT, and DCF increased by 77%, 227%, and 106%, respectively. The conversion rates of AR26, ACT, and DCF increased by 28%, 54%, and 32%, respectively, with voltage increasing from 3 V to 4 V. The data of this work will provide support for optimizing the working efficiency of UV-LED systems based on TiO2 photocatalysts. Copyright © 2024 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).